Whittaker, D. Hugh. Building a New Economy: Japan’s Digital and Green Transformation - Kawaguchi, Daiji (Journal of Economic Literature, 2025)
Daiji Kawaguchi of University of Tokyo reviews “Building a New Economy: Japan's Digital and Green Transformation” by D. Hugh Whittaker. The Econlit abstract of this book begins: “Explores institutional and ideational change in Japan and whether or not these are coming together to form a new growth model, focusing on the changing nature of the Japanese state and state–market relations, corporate governance, management and employment, education and training, and innovation and entrepreneurship.”